Treatment of partial-thickness burns with a tulle-gras dressing and a hydrophilic polyurethane membrane: a comparative study - ALPAR, ŞULE (MA HEALTHCARE LTD, 2019)
Objective: The purpose of this revisited study was to compare the clinical efficacy and long-term scar evaluation of a hydrophilic polyurethane membrane (HPM), Omiderm (Omikron Scientific Ltd., Rehovot, Israel) and an antimicrobial tulle-gras dressing (TGD), Bactigras (Smith & Nephew) in the management of partial-thickness burns. Method: Patients with partial-thickness burns were enrolled in this prospective study. Burn areas were divided into two areas and both dressings were applied to each field at the same time. Time to full re-epithelialisation and scar evaluation were compared using the Vancouver Scar Scale (VSS). Results: A total of 21 patients, mean age 36.8 years, with 22 burns areas participated. The results showed that there is no statistically significant difference in terms of full epithelialisation time in the application of either dressing (p>0.05). However, with deep dermal burns, the HPM provided slightly faster epithelialisation (p>0.05). A VSS assessment showed no statistically significant difference (p>0.05) between applying either dressing materials. Conclusion: This study indicated that both dressings had the same effectiveness in treatment of partial-thickness burn wounds. However, the use of the HPM, especially in deep dermal second-degree burns, should be one of the first-line clinical choices, based on the advantages discerned by this study.
Keywords: hydrophilic polyurethane membrane; partial-thickness burn; re-epithelialisation; second-degree burn; tulle-gras dressing; wound healing; DONOR-SITE; SKIN; OMIDERM